Electrolyte-Gated Vertical Transistor Charge Transport Enables Photo-Switching - Vieira, Douglas Henrique [UNESP]; Nogueira, Gabriel Leonardo [UNESP]; Merces, Leandro; Bufon, Carlos César Bof; Alves, Neri [UNESP] (Wiley, 2024)
Proposals for new architectures that shorten the length of the transistor channel without the need for high-end techniques are the focus of very recent breakthrough research. Although vertical and electrolyte-gate transistors are previously developed separately, recent advances have introduced electrolytes into vertical transistors, resulting in electrolyte-gated vertical field-effect transistors (EGVFETs), which feature lower power consumption and higher capacitance. Here, EGVFETs are employed to study the charge transport mechanism of spray-pyrolyzed zinc oxide (ZnO) films to develop a new photosensitive switch concept. The EGVFET's diode cell revealed a current-voltage relationship arising from space-charge-limited current (SCLC), whereas its capacitor cell provided the field-effect role in charge accumulation in the device's source perforations. The findings elucidate how the field effect causes a continuous shift in SCLC regimes, impacting the switching dynamics of the transistor. It is found ultraviolet light may mimic the field effect, i.e., a pioneering demonstration of current switching as a function of irradiance in an EGVFET. The research provides valuable insights into the charge transport characterization of spray-pyrolyzed ZnO-based transistors, paving the way for future nano- and optoelectronic applications.
Keywords: charge transport mechanism; electrolyte-gated transistor; Schottky diode; spray pyrolysis; vertical phototransistor